Identity through branding and visual semiotics the UP Sigma Beta Sorority Mindanao chapter's online scrapbook - Cubelo, Alma Kharisse G.
The purpose of this study was to create a web design for the UP Sigma Beta Sorority ?Mindanao Chapter that would reflect their identity and at the same time give information about the sorority. The UP Sigma Beta Sorority-Mindanao Chapter is one of the sorority?s chapters in the UP system. They believed that people were unaware of their identity, and at that people lacked information about them. In creating the concept for the solution to the communication problem, the researcher used Friedman?s Seven Step Method. The researcher was able to create a material through a medium that would best solve the communication problem. The researcher decided that a website would be the appropriate medium for solving the communication problem because the chosen medium for this study is often accessed by the study?s target audience. The concept for the website was a scrapbook themed website. With visual semiotics the concept of branding in mind, the researcher made sure that the chosen visual elements did not just fit the scrapbook theme, but also reflected the identity of the sorority. After conducting this study, the researcher recommends the UP Sigma Beta Sorority-Mindanao Chapter to use the created website as their official website.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Media Arts